Fluorescence-doped silica nanoparticles for ultrasensitive detection of prostate specific antigen - Msutu, Tumelo (Rhodes University, Faculty of Science, Department of Chemistry)
Prostate cancer (PCa) is the topmost diagnosed cancer in males in South Africa according to the National Cancer Registry 2020, affecting both adolescent and young adult men. Currently, PCa is diagnosed using the dreaded digital rectal examination (DRE) followed by tissue biopsy, and prostate-specific antigen (PSA) test for confirmation. DRE is an invasive method and can detect PCa in late stages when the tumour has formed. Therefore, there is a need for early diagnosis technology, that can detect PCa during carcinogenesis. PSA test offers this opportunity even though it is non-specific. This test is a non-invasive, well-established, and conventional method used as a confirmatory test. However, the test suffers from shortfalls like the misdiagnosis of benign prostatic hyperplasia (BPH) or prostatitis as prostate cancer. In this work, we have developed an ultrasensitive fluorescence-based PSA test based on the oriented immobilization of anti-PSA monoclonal and polyclonal antibodies. Anti-PSA polyclonal antibodies (anti-PSA-pAb) were bioconjugated via boronate ester onto the fluorescein-5-isothiocyanate (FITC) doped silica nanoparticles for detection. Anti-PSA monoclonal antibodies were used as capture antibodies on dark fluorescence microplate or magnetic nanoparticles. A sandwich immunoassay was used for the detection of PSA. The anti-PSA-pAb was bioconjugated on the surface of the FITC-doped silica nanoparticles. In the design, the FITC-(3-aminopropyl)triethoxysilane (APTES) organosilane precursor was encapsulated into the silica nanoparticles to form fluorescent silica nanoparticles (FITC@SiO2NPs). The silica shell prevented dye leakage and promoted fluorescent signal amplification. Optimization of the as-prepared fluorescent silica nanoparticles was investigated at altered FITC-dye loadings of 3.0% and 6.0% (for high loading). The fluorescent silica nanobioconjugates exhibited a strong excitation-dependent emission property at 518 nm and was photostable over time. The fluorescent silica nanoparticles exhibited 65% dye loading for both 3.0% and 6.0% silica nanoparticles respectively for 30 Â± 3 nm and 46 Â± 2 nm. The fluorescent nanobioconjugates' performance was evaluated using black 96-well microplates. A fluorescence sandwich-type immunoreaction was achieved via the antibody-antigen reaction of the FITC@SiO2-prAmPBA-anti-PSA-pAb/glucose nanobioconjugates binding to the captured PSA analyte. NaOH was used for alkali hydrolysis of the sensing nanobioconjugates to release the FITC-APTES molecules, leading to fluorescence signal amplification. The proposed fluorescence immunobiosensor exhibited a linear relationship between the fluorescent signals and the concentration of PSA obtained in the range of 2.0 pg.mL-1 to 50 ng.mL-1, with excellent limit of detection and limit of quantification both in the pg.mL-1 range in PBS buffer (pH 7.4) and PSA in spiked serum samples. The immunosensor was based on the immunometric sandwich protocol, using nanomagnetic-silica antibody bioconjugates for capture and fluorescent nanobioconjugates as sensing probes. The use of nanomagnetic-silica antibody bioconjugates allowed concentration of PSA as the analyte and ease of separation using a magnet. Alkali hydrolysis of the sensing fluorescent nanobioconjugates is achieved using NaOH, resulting in the release of FITC molecules and an amplified fluorescence detection signal. The analytical performance of the proposed fluorescence immunobiosensor exhibited a linear relationship between the fluorescent signals and the concentration of PSA obtained in the range of 2.0 pg.mL-1 to 100 ng.mL-1, with excellent limit of detection and limit of quantification both in the pg.mL-1 range in PBS buffer (pH 7.4) and PSA in spiked serum samples. The immunosensor also exhibited good specificity and selectivity for PSA with 94.8% - 102.5% recovery rates. The proposed fluorescence immunoassay exhibited high selectivity and specificity for the detection of PSA.
Keywords: Nanoparticles; Ferric oxide; Prostate-specific antigen; Prostate -- Cancer -- Diagnosis; Fluorescence microscopy